Rekrument SDM Dalam Membangun TQM - Maya Sri Rahayu; Jamilus (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Recruitment of educators and education personnel in a school, generally based on needs. The goal is to get qualified educators and education personnel who meet certain criteria to teach or work in the institution. In the recruitment process, educational institutions will look for teacher candidates (HR) who have educational backgrounds and experience that match the required conditions. In addition, Educational Institutions also want to obtain teacher candidates who have an interest and passion in teaching and are able to contribute to Educational Institutions. By having qualified educators, educational institutions can provide good and effective education for students. The research method used is qualitative research with a field research approach. Observation, interviews and documentation are data collection techniques carried out by researchers themselves by making appointments and visiting research locations, namely SMP IT Al Bina – Dharmasraya. After passing a series of selection tests in accordance with the operational standards for recruitment implementation set by the Foundation and the school, prospective applicants who are accepted will be contacted by the Foundation for signing an employment contract.